Haiti : Use of Fund Resources-Request for Emergency Post-Conflict Assistance. (IMF Staff Country Reports; Country Report ;, 2005)
This paper discusses Haiti's Request for Emergency Post-Conflict Assistance (EPCA). The authorities' program draws on a broad reform and development program prepared in collaboration with the international community. The principal objectives of the program are to strengthen key institutions and governance, promote economic recovery, improve access to basic services, restore security, and promote national dialogue. In the IMF staff's view, Haiti meets the criteria for IMF assistance under the EPCA. The proposed purchase under the IMF's EPCA policy is for SDR 10.23 million.